Przeprowadzenie dowodu za pomocą środków porozumiewania się na odległość na zasadzie art. 235 § 2 KPC a realizacja zasady bezpośredniości – uwagi w kontekście nowelizacji KPC z 10.7.2015 r. – część 1 - Budniak-Rogala, Aleksandra (Wydawnictwo C.H. Beck, 2017)
This paper constitutes an attempt to present comprehensive interpretation of the Article 235 of the Polish Code of Civil Procedure in the light of the directness principle and by taking into account, in particular, modifications introduced by the Act of 10 July 2015 on Amending the Civil Code, Code of Civil Procedure and certain other acts (Dz.U. [Journal of Laws] item 1311), which entered into force on 8 September 2016. The paper has been divided into two parts. Preliminary remarks of the first part of the paper present the outcomes of the directness principle application in the course of civil proceedings, as stipulated in the Article 235 § 1 in principio of the Code of Civil Procedure. Further, the paper discusses premises for taking evidence by the delegated judge or requested court pursuant to the Article 235 § 1 of the Code of Civil Procedure as an exception to the said principle. Subsequently, the author comments taking evidence by using means of distance communication as provided for in the Article 235 § 2 in the Code of Civil Procedure – both in the wording before and after the provisions of the abovementioned amendment entered into force. It is worth mentioning that according to the amendment the Legislator deleted second sentence of the Article 235 § 2 of the Code of Civil Procedure, by which the adjudicating court was obligated to take this evidence in presence of requested court or registrar of this court. In the author`s opinion this modification should be considered as a positive change. Same positive opinion should be given to the institution of taking evidence remotely. In the second part of the paper the author describes relations between admissibility of taking evidence by delegated judge or requested court (Article 235 § 1 of the Code of Civil Procedure) and taking evidence remotely (Article 235 § 2 of the Code of Civil Procedure) as well as between taking evidence outside the courthouse (Article 235 § 2 of the Code of Civil Procedure) and conducting a remote hearing (Article 151 § 2 of the Code of Civil Procedure). The paper discusses also the statutory delegation of power laid down in the Article 235 § 3 of the Code of Civil Procedure. The performed analysis leads to the conclusion that taking evidence by using means of distance communication actually strengthens execution of the directness principle in the civil procedure.
Keywords: directness principle; remotely taken evidence; judicial assistance